Aceitação de tecnologia em um governo estadual: uma análise do uso de um sistema de gestão eletrônica de documentos - Grecco, Larisse Brunoro (2023)
Modernization policies in the public sector have improved services and allowed greater approximation between citizens and governments. In this sense, in 2019, the e-Docs System was instituted in all sectors of the Government of Espírito Santo, intended for the Management of electronic archival documents of the State. It was noted, however, that its use did not occur equally among the servers, with no studies regarding its acceptance by users. In this context, the main objective of the project was to analyze the relationships between the intention to use the e-Docs System and the psychosocial factors that precede it. The proposed analysis model was based on the Unified Theory of Acceptance and Use of Technology (UTAUT). As for the methodology, it consisted of quantitative and descriptive research, whose data were collected from a questionnaire applied to Government servants. Analyzes based on the method of structural equation modeling by partial least squares demonstrated that the psychosocial factors attitude, performance expectations and facilitating conditions precede and affect the intention to use the e-Docs system. The results indicate the importance of disclosing data that portray the productivity gains arising from the use of the system, as well as the existence of service and support channels for users.